(untitled) (Journal of Geography and Environmental Management, 2017)
This paper considers determination of statistical parameters for spring flood runoff by the river basin of Sarysu, for the long-term period. The main parameters of distribution curve determining calculation hydrological characteristics are the norm of runoff and coefficient of variation. In case of purpose of various water management actions in the basin, it is necessary to know reliability of these parameters. Data are provided in four options: according to actual data of observations of water discharge, on (1940-2012) given to the long-term period, for the last thirty-eight-year period (1975-2012) and for the conditional and natural period (1940-1974). It presents a series of observations made for the long-term period, determines statistical parameters for the depth of spring flood runoff as well as constructs the probability curves of the depth of spring flood runoff by study areas. The paper also gives an estimation of the probability values of the depth of spring flood runoff for the calculation period and for the last period.